(untitled) (Journal of actual problems of jurisprudence, 2018)
In the real advanced study some questions of the legal adjusting of legal position of participants of civil procedure are examined in РК. During research scientific conclusions and analysis of operating гражанского of judicial legislation are done in the areas of the legal adjusting of legal position of participants, and judicial representatives in civil procedure. Key words: trial, persons participating in business, parties, advocate, judicial representative, lawyer.